Rotavirus-Induced Expansion of Antigen-Specific CD8 T Cells Does Not Require Signaling via TLR3, MyD88 or the Type I Interferon Receptor - Muleta, Konjit Getachew; Ulmert, Isabel; Hamza, Kedir Hussen; van Dijl, Sharné; Nakawesi, Joy; Lahl, Katharina (Frontiers in Immunology, 2022)
Rotavirus (RV) infection induces strong adaptive immunity. While protection from reinfection requires humoral immunity, initial clearance of infection depends on cytotoxic CD8 T cells. Type I classical dendritic cells (cDC1) excel at CD8 T cell induction through cross-presentation and are essential for optimal cytotoxicity towards RV. Upon sensing of infection-induced innate immune signals through pattern recognition receptors (PRRs), cumulating in autocrine type I interferon (IFN) signaling, cDC1 mature and migrate to the draining lymph nodes (LNs), where they prime adaptive immune cells. To analyze which PRR pathways lead to robust cytotoxicity in the context of RV infection, we measured RV-specific CD8 T cell priming in mice deficient for Toll-like receptor 3 (TLR3), recognizing double-stranded RNA, or for MyD88, the adapter for all other TLRs and IL-1 family cytokines. Individual TLR3- and MyD88-mediated signaling was not required for the priming of CD8 T cell responses to RV and neither deficiency impacted on RV clearance. Surprisingly, the accumulation of RV-specific CD8 T cells was also not altered in the absence of type I IFN signaling, while their ability to produce IFNγ and granzyme were blunted. Together, this suggests a substantial level of redundancy in the sensing of RV infection and the translation of signals into protective CD8 T cell immunity.